Effects of biodiesel on a low heat loss diesel engine - Hazar, Hanbey (Pergamon-Elsevier Science Ltd, 2009)
In this study, the cylinder head, exhaust, and inlet valves of a diesel engine were coated with the ceramic material MgO-ZrO2 by the plasma spray method, while the piston surface was coated with ZrO2. Thus, a thermal barrier was provided for the elements of the combustion chamber with these coatings. Using identical coated and uncoated engines, the effects of canola methyl ester produced by the transesterification method, and ASTM No. 213 fuel on engine performance and exhaust emissions were studied. Tests were performed on the uncoated engine, and then repeated on the coated engine and the results were compared. An increase in engine power and decrease in specific fuel consumption, as well as significant improvements in exhaust gas emissions and smoke density, were observed for all test fuels used in the coated engine compared with that of the uncoated engine. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Low heat rejection engine; Biodiesel; Emissions